1993
DOI: 10.1021/bi00092a023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-modulated complex formation between .alpha.-glycerophosphate dehydrogenase and lactate dehydrogenase

Abstract: A modified Hummel-Dreyer equilibrium chromatography technique was used to test the hypothesis that NADH induces the molecular association of lactate dehydrogenase (LDH) and alpha-glycerol-3-phosphate dehydrogenase (alpha-GDH). In the presence of a very limited NADH concentration, a unique elution profile with a new peak running immediately ahead of a trough at the free alpha-GDH elution position is obtained. The appearance of this peak-trough profile is physical evidence that reversible association between LDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…The CheW concentration in the sample at which there was no resulting CheW peak or trough represented a sample at true equilibrium. From this, they could calculate a dissociation constant of the complex of 13 M. A similar series of experiments was done by Yong et al (243) to demonstrate an interaction between glycerol-3-phosphate dehydrogenase and lactate dehydrogenase over an extremely limited range of NADH concentrations. Such a complex was observed only when the NADH concentration was high enough for an interaction and low enough to be shared by the two enzymes, and it provided evidence for substrate channeling.…”
Section: Methods For Determining Binding Constantsmentioning
confidence: 82%
“…The CheW concentration in the sample at which there was no resulting CheW peak or trough represented a sample at true equilibrium. From this, they could calculate a dissociation constant of the complex of 13 M. A similar series of experiments was done by Yong et al (243) to demonstrate an interaction between glycerol-3-phosphate dehydrogenase and lactate dehydrogenase over an extremely limited range of NADH concentrations. Such a complex was observed only when the NADH concentration was high enough for an interaction and low enough to be shared by the two enzymes, and it provided evidence for substrate channeling.…”
Section: Methods For Determining Binding Constantsmentioning
confidence: 82%
“…The influence of CP (and other substrates) on complex formation is worth further investigation. Using Hummel-Dreyer equilibrium chromatography, Yong et al (1993) found a metabolite modulated enzyme-enzyme interaction: the reversible association between lactate dehydrogenase and α-glycerol-3-phosphate dehydrogenase was shown to occur over a limited range of NADH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, Yong et al (1) reported detecting a strong complex (K a ) 2.0 ( 0.6 µM -1 ) in the presence of a very limited substoichiometric [NADH], a condition not tested in previous studies. The detection of a weak complex (K a ) 0.04 ( 0.02 µM -1 ) in the absence of NADH, but not in the presence of a saturating [NADH], was also reported (1). This NADH-modulated association suggested an unprecedented but reasonable mechanism of enzyme interactions of potentially great importance to enzyme modulation and the controversial phenomena of direct NADH transfer (channeling) between dehydrogenases (for review, ref 4).…”
mentioning
confidence: 95%
“…Previous attempts to detect a complex between these two dehydrogenases were unsuccessful (2,3). However, Yong et al (1) reported detecting a strong complex (K a ) 2.0 ( 0.6 µM -1 ) in the presence of a very limited substoichiometric [NADH], a condition not tested in previous studies. The detection of a weak complex (K a ) 0.04 ( 0.02 µM -1 ) in the absence of NADH, but not in the presence of a saturating [NADH], was also reported (1).…”
mentioning
confidence: 97%
See 1 more Smart Citation